STRENGTHENING COMMUNITY UNITY AND UNITY THROUGH PRESERVING BEJAMU SAMAN ART - Melia; T Misbah Lembong; Rusnawati (Indonesian Journal of Education (INJOE), 2024)
The bejamu saman art in Gayo Lues has a uniqueness that is not found in other arts, namely that it is able to strengthen the unity and unity of society. The aim of this research is to explain the unity and integrity of the Gayo Lues community from the preservation of Bejamu Saman art, explain the uniqueness of Bejamu Saman art which differentiates it from other arts, and to find out the importance of Bejamu Saman art for the Gayo Lues community. The method used in this research is a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The results of the research show that in the process of implementing this Bejamu Saman art, it can strengthen the unity and integrity of the community, because the Bejamu Saman art can knit ties of friendship because in this Bejamu Saman art invites people from other villages to come and stay for two days and two nights in their village. and the occurrence of social contact in society because preparation for the implementation of this art requires close cooperation. The art of Bejamu Saman is also unique, so this art attracts a lot of public attention. The uniqueness of this bejamu saman lies in its poetry which contains songs with the theme of the human relationship with Allah SWT and its movements produce sounds that are beautiful to hear and each movement of the saman contains meaning as an instruction for the next movement that will be played.